Deadline for examining an application for security in Czech and Polish civil proceedings - Zemandlová, Anna; Drozdowicz, Krzysztof (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The article aims to analyse the issue of the deadline for examining an application for security in Czech and Polish civil proceedings. The comparative law method was used in the work. The publication compares normative solutions regarding the deadline for examining an application for security in the Czech Republic and Poland. The article presents an analysis of special solutions used by the legislator in selected cases where it is necessary to schedule a hearing or accelerate the consideration of an application for security. The issue of the consequences of considering an application for security in violation of the deadline set by the legislator is raised. The research conducted allowed the following conclusions to be drawn. In both Polish and Czech civil proceedings, security proceedings are an independent part of the proceedings, separated from enforcement proceedings. In both legal systems, the deadline for examining an application for security is advisory, and exceeding it does not result in any sanctions. In Czech civil proceedings, applications for security are not examined at a hearing, while according to Polish regulations it is obligatory in some cases. In the Czech Republic, there are two types of special security measures for the immediate protection of children and against domestic violence. Polish legislation seems to be more flexible and better protects the procedural rights of the parties than the Czech Code of Civil Procedure. The presented analysis may contribute to the discussion on possible changes in the provisions of civil procedural law in Poland and the Czech Republic.